Management of orepasses in poor ground: learnings from Carrapateena sublevel cave - O.'Bree, M.; Karn, S.; Peters, C.; Aslin, J. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
At Carrapateena orepasses are a critical component of the material handling system, connecting sublevel cave (SLC) production levels to the primary crusher. Four orepasses were developed for efficient ore movement in the production ramp-up phase of the SLC, however, poorer than expected ground conditions created challenges for continual safe access and use of this infrastructure. Two of the northern orepasses (MAP-200 and MAP-300) experienced overbreak of 2–3 times the design diameter within the first months of use, threatening productivity and safe access in a spatially constrained mine plan. A robust management system utilising LiDAR scanning, strict pass level control, extensometer monitoring and additional cable bolt support was successfully implemented, enabling productive use of these passes without lining or extensive rehabilitation.